ANALISIS DAMPAK BENCANA KABUT ASAP KEBAKARAN HUTAN DAN LAHAN TERHADAP PDRB SEKTOR TRANSPORTASI ANGKUTAN UDARA DI PROVINSI RIAU TAHUN 2005 – 2014 - Chandra, Doni Wijaya; Ekwarso, Hendro; Isbah, Ufira (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the impact of Haze Disasters of Land and Forest Fires to the GDP of Air Transport Sector in Riau Province Period 2005 to 2014. This study uses secondary data obtained from the website of the Ministry of Environment and Forests Indonesia, the Central Bureau of Statistics Riau and PT. Angkasa Pura II Pekanbaru. This research uses descriptive quantitative method, and analyzed using a multiple linear regression analysis using a Eviews program. The study consists of one independent variable (Extensive Land and Forest Fires), a variable dipendent (GDP of Air Transport Sector) and two control variables (Total Number of Passengers and Cargo). The researcher conducted a research data transformation into a logarithm to overcome the autocorrelation on this study. The results obtained are Extensive Land and Forest Fires, Number of Passengers and Cargo simultaneously influence the GDP of Air Transport Sector in Riau Province with a significant level of 10% was obtained probability value of F-statistic < α (0.1) ie 0.000530 < α (0.1). Partially Extensive Land and Forest Fires does not have a significant effect on the GDP of Air Transport in the Riau Province, this is because the haze disastrous of land and forest fires only occurs temporarily.Variation factors that influence the GDP of Air Transport Sector can be explained by the Extensive Land and Forest Fires, Number of Passengers and Cargo is equal to 93.7168% (0.937168 R-squared value) while the rest of 6.2832% is explained by other variables outside the research.Keywords: GDP, Air Transport, Disaster, Haze